Stability of Tetraglyme for Reversible Magnesium Deposition from a Magnesium Aluminum Chloride Complex. Issue 2 (1st January 2019) - Hegemann, P.; Hegemann, M.; Zan, Lingxing; Baltruschat, H.
Abstract : The electrochemical behavior of Mg deposition and stripping at Au-electrode in magnesium aluminum chloride complex (MACC) tetraglyme electrolyte has been studied using differential electrochemical mass spectrometry (DEMS) and scanning tunneling microscopy (STM). During Mg deposition no dendrites are formed. MACC electrolyte supports reversible Mg deposition with high coulombic efficiency. Despite of the high coulombic efficiencies that has been observed in MACC, appreciable ethylene formation due to the decomposition of tetraglyme has been detected solely during Mg stripping. The mechanism of organic solvent decomposition will be discussed. This ethylene formation is quantitatively responsible for the missing charge balance of Mg-deposition and dissolution. Possible origins will be discussed.